Miguel Baraona Cockerell: The Plot and the Threads. Capitalist Modernization and the Four Spirals of Modernity. EUNA 2016 - Rincón Soto, Lucía (2017)
This paper develops the line of thought of Miguel Baraona Cockerell, present in his book The Plot and the Threads. Capitalist Modernization and the Four Spirals of Modernity. In this book, he broadly argues that globalization, modernization, conflict and resistance are an intrinsic part of modernity. This chain of events has led to a spiral of problems which threaten the existence of mankind; problems explained in such a convincing way by the author. His criticism of the capitalist system puts in evidence the urgency for a change in mentality, a new humanism which will be implemented, as far as possible, from the confluence of social movements with a conscience leaning toward the creation of a possible world.